Pengembangan Sekolah Adiwiyata Di SMPN 1 Ujan Mas Kabupaten Kepahiang - Rismaida; Somantri, Manap (UNIVERSITAS BENGKULU, 2023)
This study aims to describe the performance of teachers in online learning during the Covid-19 pandemic at SMP N 11 Rejang Lebong. This research is a case study research. The research was conducted at SMP Negeri 11 Rejang Lebong Regency. Research data obtained from interviews, observations and documentation. Research data analysis includes data reduction, data presentation, verification and conclusion drawing. Results showed that teacher's performance in online learning during the Covid-19 pandemic at SMP N 11 Rejang Lebong, among others, was seen from: (1) Teacher motivation was shown by the continuity of learning and teaching activities carried out online, teachers felt proud to be able to plan, implement, carry out assessments and follow-up in assignments as teachers, starting from the beginning of the entry of the Covid-19 virus until now; (2) Teacher discipline is shown by the implementation of the duties and obligations of teachers in online learning that has complied with the rules and ethics that apply in schools; (3) The professional competence of teachers is demonstrated by developing an online learning implementation plan (RPP), mastering learning materials, as well as developing teaching materials and online learning media; (4) The follow-up taken by the teacher is indicated by efforts to improve learning which will be carried out as an effort to improve the quality of learning. Based on the results of the study, it is suggested that efforts should be made to increase teacher motivation in carrying out teacher duties in online learning during the Covid-19 pandemic